أسلوب المحاجة العقلانية مع أهل الكتاب في سورتي البقرة وآل عمران = Method of the rational argumentation with people of the book in Surah Al-Baqarah and Ali ‘Imran - Elatrash, Radwan Jamal Yousef; Banaderi, Farzaneh Balali; Shkokani, Najwa Naief (Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), International Islamic University Malaysia, 2018)
يهدف هذا البحث إلى إبراز أسلوب المحاجة العقلانية مع أهل الكتاب في سورتي البقرة وآل عمران، وذلك بمناقشة بعض المسائل الدعوية الواردة فيهما، وإظهار شخصية أهل الكتاب فيها، من خلال صُور من تصرفاتهم، وإنّ دعوة أهل الكتاب يجب أن تكون بأساليب مؤثرة كأسلوب المحاجة العقلانية؛ ويكون اعتقادات المنحرفة الفاسدة والتي منعتهم أهل الكتاب من قب ول الحق والدخول في الإسلام، كادعاءهم بأن الله فقير وغيرها. وهذا أسلوب هو من وسائل دعوتهم مما يدعوهم للتفكر ومراجعة النفس، كما فيه من تحليلٍ للواقع، واستخدام العقل، ولإقامة الحجة عليهم باستخدام المنهج الاستقرائي والتحليلي وذلك من خلال جمع المعلومات من المصادر القديمة والحديثة المتعلقة بالموضوع، والآيات القرآنية التي وردت فيها أسلوب المحاجة العقلانية مع أهل الكتاب من خلال سورتي البقرة وآل عمران، وتحليلها والاستفادة منها. وخلصت إلى نتيجة أن السو رتان تزخران بأسلوب المحاجة العقلانية مع أهل الكتاب، وأن المسلم المعاصر يستطيع أن يستفيد من ذلك الأسلوب في أي زمانٍ ومكانٍ مراعياً أحوال هؤلاء المدعويين وظروفهم. ***************************************************** The purpose of this research is to highlight the method of rational argument with the people of the book in the Surat al-Baqarah and Ali ‘Imran. It discusses some of the religious issues contained in them and to show the personality of the people of the book and their actions. However, the call of the people of the Book must be made by influential methods. For instance, the corrupt deviant belief that God is poor, among others. Prevent them from accepting and entering into Islam. Therfore the method encourages them to have a rethink and a review of themselves. Also the analysis of reality, the use of reasoning, and establishment of argument using the method of inductive and analytical reasoning by collecting information from ancient and modern sources related to the subject, and the Quranic verses in which the method of rational argument with the people the book in the two sections of the cow and Ali ‘Imran, analyzed and used. Thus, it concludes that the chapters are rich in rationalist argument with the people of the book, and that the contemporary Muslim can benefit from the method at any time and place, taking into account, of these invitees and their circumstances.